Pentingnya Konsumsi Tablet Fe Pada Ibu Hamil - Hasriana; Natalia Ida Kartanti; Rahma Yulis; Ramdya Akbar Tukan; Gusni Fitri; Darni; Najihah; Dewi Wijayanti; Ana Damayanti (PT. Penerbit Riset Sadwa, 2025)
Anemia during pregnancy remains a public health problem that increases the risk of complications for both the mother and the fetus. One of the preventive efforts recommended by the government is the regular consumption of iron (Fe) tablets throughout pregnancy. This community service activity aims to improve the knowledge and awareness of pregnant women regarding the importance of consuming Fe tablets and to encourage adherence to the recommended intake. The activity was carried out through health education sessions, interactive discussions, and the distribution of educational leaflets to pregnant women in the Puskesmas Gunung Lingkas Kota Tarakan date 28 Juny 2025. Evaluation was conducted using pre-tests and post-tests to measure participants’ knowledge improvement. The results showed a significant increase in participants’ understanding of the function of Fe tablets, appropriate dosage, proper timing of consumption, and their impact on preventing anemia during pregnancy. In addition, most participants expressed their commitment to consuming Fe tablets regularly. This community service initiative is expected to contribute to reducing the prevalence of anemia among pregnant women and improving the overall health of mothers and their babies.